The Effect of Parents and Environment on Students' Learning Motivation - Reski Nofrialdi (Green Publisher, 2022)
This study aims to examine the Effect of Parents and Environment on Student’s Learning Motivation (Education Management Literature Review). Within the scope of school education, the existence of the principal is the determinant and direction of school policy. The principal must also have the ability to regulate his agency in order to achieve and realize the agency's goals. In this study, researchers used descriptive qualitative methods and library research. By reviewing previous articles that are relevant to this research. The results of this study are: 1) Parents has an effect on Student’s Learning Motivation, and 2) Environment has an effect on Student’s Learning Motivation.